Community mental health - Ritter, Lois A.; Lampkin, Shirley Manly (Jones & Bartlett Learning, 2012)
Foundations of community mental health and illness -- Fundamentals of mental illness -- Culture and mental health -- Legal and ethical issues in mental health practice -- The mental health care system -- Children, adolescents, and mental health -- Early and middle adulthood and mental health -- Older adults and mental health -- Community mental health problems : environment -- Community mental health problems : substance abuse -- Community mental health problems : violence -- Community mental health problems : violence across the lifespan -- Prevention and health promotion in community mental health -- A vision for the future